Flustrellidra armata (Bryozoa: Ctenostomatida)—a new species from the southern shoreline of Korea - Grischenko, Andrei V.; Seo, Ji Eun; Min, Bum Sik (Zootaxa, 2010)
Flustrellidra armata sp. nov. is described from ten intertidal and four subtidal sites along the southern coast of Korea. The new species possess a series of small lateral and occasionally proximal kenozooids with simple spines; large scattered vicarious kenozooids with long, tubular, sharp or weakly ramified spines; and a marginal fringe of spiny kenozooids. Colonies of F. armata provide a habitat for a large number of associated benthic organisms. This species is an abundant and prominent component of rocky intertidal to upper subtidal communities and is the third species of Flustrellidra with low-Boreal to Subtropical distribution.